Climate characterization and classification of the River Uruçuí Preto hydrographic basin, PI – Brazil (Research, Society and Development, 2022)
Given the lack of climatological information on the Uruçuí Preto river basin, its climatic characterization was carried out. The results showed water deficit in April and November, as well as water surplus in February and March with 39.2 and 30 mm. Annual evapotranspiration is 1,548.9 mm and evaporation is 905.5 mm/year. Annual temperature 26.1 °C. The method adopted to obtain the classification is that of the water balance that presents a rainy scenario with the classification of dry sub-humid, regular and medium scenario with a semi-arid classification and in the dry scenario with the classification of arid in the basin. The average monthly temperature was maximum in September and minimum in January; The moisture content is 0.09%, the aridity index is 0.42% and the water content is -0.20%; The method adopted to obtain the classification is the water balance proposed by Thornthwaite (1914) and Thornthwaite et al., (1948, where four rainfall scenarios were used: in the rainy scenario as a dry sub-humid classification, regular and medium scenario with a classification semiarid and in the dry scenario with the classification of arid; According to the Köppen climate classification, two climatic types are distinguished in the hydrographic basin of the Uruçui Preto River or Aw, hot and humid tropical, with rains in the summer and dry in the winter; BSh, semi-arid hot, with summer rains and dry winters.